The effectiveness of using Wattpad to teach narrative text writing - Gustiani, Rayna Elisya; Bunau, Eusabinus; Rahmani, Eka Fajar (English Learning Innovation, 2024)
This study aimed to examine the effectiveness of Wattpad as a medium to teach narrative text writing to the tenth-grade students of SMK Negeri 5 Pontianak.  This study was carried out using a pre-experimental study with one group pre and post-test design. The sample of this research was a cluster involving 30 students from Class X Tata Kecantikan I taken from a population of 334 students. The results indicated that the t-test was 12.489. The analysis of the pre-post-test scores indicated that the pre-test was lower than the post-test (71.5<88.3). The t-test analysis showed a greater value compared with the t-table (12.489>2.045) with the degree of freedom 29 and ???? = 0.05. The analysis revealed that the null hypothesis was rejected while the alternative hypothesis is accepted. In addition, the effect size was categorized as a strong effect with the value (2.28>1.00). Therefore, the research referred that the use of Wattpad as a medium to teach students narrative text writing was effective with a strong effect. Despite its initial purpose, Wattpad can be a recommended media to teach tenth-grade students.